(3GdLhgQ GdfVjO aj TQM efWb GdJLQjOs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3QVG Hf eTchQs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdeJaQO HhLhH GdhLhO (B... (3aTQYJ aj EedGA gPG GdcJGH GdehShe (B... (3dEHGfI eTcdGJg hJMdjd eYVdGJgs
(3BNQgG (B:s
(3BNQgG(B: (3hCfhGY GdeNjdGJ aj GdbjGSGJ GdTYQjI (B... (3cdeG cGfJ CZQH cGfJ CdP hGYLH adG jecf VHWgG ceG Cecf VHW GdehGVY aj GdUfGYJjf GdChdJjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 227s
(3GdPQjYI, L (B5: 206s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds